Emotions in Second Language Teaching Theory, Research and Teacher Education (Springer International Publishing, 2018)
This edited volume explores the multifaceted nature of teacher emotions, presenting current research from different approaches and perspectives, focused towards the second language classroom. Twenty three chapters by well-known scholars from the applied linguistics, TESOL and educational psychology fields provide the reader with a holistic picture of teacher emotions, making this collection a significant contribution to the field of second language teaching. Given the emotional nature of teaching, the book explores a number of key issues or dimensions of L2 teachers' emotions that were until now rarely considered. The contributions present the views of a select group of applied linguistic researchers and L2 teacher educators from around the world. This international perspective makes the book essential reading for both L2 teachers and teacher educators. This book will quickly become the "go to" text for anyone interested in learning about the integral--if not foundational role--of emotions in language teaching practice. The authors in this volume address a wide range of topics, discuss diverse scholarly influences, and demonstrate numerous research methods that can be used in deepening our understanding of emotions in language teaching. Its breadth and depth of coverage make the book a useful and attractive resource for second language researchers, language teacher educators, and language teachers. Elizabeth Miller, University of North Carolina at Charlotte, USA.